2022
DOI: 10.1088/1755-1315/954/1/012070
|View full text |Cite
|
Sign up to set email alerts
|

Development of formulation for soft cheese based on milk from animals of different species

Abstract: One of the core branches of the Russian farming industry is the dairy industry. Cheese has always ranked first in nutritional profile and calorie count. It is high in fat, protein, minerals and vitamins. All these components are in balanced proportions and are easily absorbed by the human body. In Russia, the most consumed is cow cheese; goat cheese is also gaining popularity; in the Caucasus – goat and sheep milk cheese. Cheese made from milk of different agricultural animals each has its own quality indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
2
4
0
Order By: Relevance
“…Some of them have identified representatives of Enterococcus, Lactobacillus, Streptococcus, Lactococcus, and Pediococcus. The present study found no pathogenic microorganisms, which confirmed the fondings reported by some authors [2,4,5,21,22]. Other authors [5] report on artisanal cheeses in which molds and yeasts have a higher availability in the ripening process due to the penetrating air in the vessel (Tulum).…”
Section: Results and Duscussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Some of them have identified representatives of Enterococcus, Lactobacillus, Streptococcus, Lactococcus, and Pediococcus. The present study found no pathogenic microorganisms, which confirmed the fondings reported by some authors [2,4,5,21,22]. Other authors [5] report on artisanal cheeses in which molds and yeasts have a higher availability in the ripening process due to the penetrating air in the vessel (Tulum).…”
Section: Results and Duscussionsupporting
confidence: 91%
“…The total protein concentration of 16.44% on the 45th d of ripening increased by about 8.0% respectively for the same ripening stage; the total nitrogen increased by about 9.3%. The increase in nitrogen fractions during cheese storage has also been reported by other researchers [10,20,21], and their studies stated that those storage methods significantly affected nitrogen concentrations. The decrease in water content during ripening is related to the created biochemical processes and binding of free water in protein matrices.…”
Section: Results and Duscussionsupporting
confidence: 75%
See 3 more Smart Citations